Tesco: how supply chain strategy supports retail success - Sparks, Leigh (Henry Stewart Talks, 2019)
This case study analyses the supply chain strategy of Tesco, one of the biggest retailers in the UK. It describes the different approaches they took over the years, and asks what the implications are for Tesco’s ongoing success after 40 years of leadership in the retail domain.